1991
DOI: 10.1093/jmedent/28.2.246
|View full text |Cite
|
Sign up to set email alerts
|

Rubidium for Marking Adults of Culicoides variipennis (Diptera: Ceratopogonidae)

Abstract: Culicoides variipennis adults were reared from media with nine concentrations of rubidium (Rb) ranging from 0.0 to 1,000 ppm. Rubidium levels were measured using an atomic absorption spectrophotometer. Concentrations of 500 and 1,000 ppm of Rb reduced pupal production, adult emergence, and adult longevity; lower levels of Rb had no noticeable effects. Adult females reared from media containing 15.6 ppm Rb were marked for a period of at least 13 d, and Rb levels were unaffected by a blood meal on day 3. One mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Culin and Alverson (1986) found that adult male Helicoverpa zea (Boddie) fed on artiÞcial nectar spiked with 5,000, 10,000, or 20,000 g/g RbCl retained signiÞcant marker for up to 12 d postfeeding. Holbrook et al (1991) found that adult females of the biting midge reared on media containing 15.6 g/g Rb were marked for a period of at least 13 d. Cohen and Jackson (1989) found that 28% of the average Rb concentration remained after 7 d, but only 7.4% of the original Rb concentration remained after 14 d in Geocoris punctipes (Say). Frazer and Raworth (1974) found that in adult pea aphids, Acyrthosiphon pisum (Harris), 77% of Rb was lost within 2 d of leaving the source plant but that detectable quantities were present for 4 d. Guillebeau et al (1993) reported that the level of Rb in green peach aphid, Myzus persicae (Sulzer), and potato aphid, Macrosiphum euphorbiae (Thomas), was reduced by nearly 90% after a 5-d removal from the tomato plants treated with 10,000 g/g RbCl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culin and Alverson (1986) found that adult male Helicoverpa zea (Boddie) fed on artiÞcial nectar spiked with 5,000, 10,000, or 20,000 g/g RbCl retained signiÞcant marker for up to 12 d postfeeding. Holbrook et al (1991) found that adult females of the biting midge reared on media containing 15.6 g/g Rb were marked for a period of at least 13 d. Cohen and Jackson (1989) found that 28% of the average Rb concentration remained after 7 d, but only 7.4% of the original Rb concentration remained after 14 d in Geocoris punctipes (Say). Frazer and Raworth (1974) found that in adult pea aphids, Acyrthosiphon pisum (Harris), 77% of Rb was lost within 2 d of leaving the source plant but that detectable quantities were present for 4 d. Guillebeau et al (1993) reported that the level of Rb in green peach aphid, Myzus persicae (Sulzer), and potato aphid, Macrosiphum euphorbiae (Thomas), was reduced by nearly 90% after a 5-d removal from the tomato plants treated with 10,000 g/g RbCl.…”
Section: Discussionmentioning
confidence: 99%
“…Stimmann et al (1973) found slower larval development of cabbage looper on a diet with Rb concentrations of up to 70,000 g/g; however, the rate of pupal development was unaffected. Holbrook et al (1991) found that 500 and 1000 g/g Rb in the rearing media of the biting midge Culicoides variipennis (Coquillett) reduced pupal production, adult emergence, and adult longevity. In our study, there seemed to be only minor effects associated with the use of RbCl and CsCl at 1000 g/g in the meridic diet.…”
Section: Discussionmentioning
confidence: 99%
“…It was an excellent marker because ingestion of Rb did not have an adverse effect on survival of nymphs at concentrations between 1000 and 5000 ppm, was not immediately excreted and was retained in the tissues at detectable levels for up to two weeks. Rb has also been used in a variety of insect feeding and dispersal studies (Van Steenwyk, 1978;Holbrook et al, 1991;Holbrook, 1995;Corbett et al, 1996;Woods and Streett, 1996 a, b;Coll et al, 1997;Woods et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Holbrook et al (1991) successfully cultured Culicoides sonorensis Wirth & Jones (Diptera: Ceratopogonidae) in RbCl‐treated water and detected Rb in adult females through to day 13. Rubidium has also been used for marking Anopheles stephensi by culturing the larvae in various concentrations of RbCl in water (Solberg et al , 1999).…”
Section: Introductionmentioning
confidence: 99%